Heating sensation in patients with and without spinal fixation devices during MRI examination at different magnetic field strengths. Issue 2 (14th October 2018) - Yamaguchi, Taiki; Abe, Yuichiro; Ichino, Yoshio; Satoh, Shigenobu; Masuda, Takeshi; Kimura, Shoichi; Ito, Manabu; Yamamoto, Toru
Abstract : Background: Radiofrequency (RF) heating during MRI theoretically increases with magnetic field strength. In addition, implanted metallic devices are reported to further increase RF heating. However, a detailed evaluation of this type of heating remains scarce in clinical practice. Purpose: To assess possible risks and discomfort related to RF heating during MRI examinations of patients with and without metallic implantable devices. Study Type: A retrospective study of previous questionnaire results on the heating sensation during MRI examinations of the lumbar spine. Subjects: In all, 715 patients, of whom 101 had implanted lumbar spine fixation devices. Field Strength/Sequence: 1T and 3T/T1 ‐ and T2 ‐weighted imaging. Assessment: The number of patients who perceived heating around the lumbar spine or other regions during the MRI examination. Statistical Tests: A chi‐square test with respect to static field strength B0, presence of lumbar spine fixation devices, and duration of the MRI examination. Results: The number of patients who perceived heating around the lumbar spine during the MRI examination significantly increased from 5.0% at 1T to 47.5% at 3T ( P < 0.001), without a significant difference between patients with and without lumbar spine fixation devices ( P = 0.23 at 1T, P = 0.48 at 3T), and regardless of the duration of the MRI examination ( P = 0.88 at 1T, P = 0.15 at 3T). Data Conclusion: Sensation of RF heating increased by around 10 times from 1T to 3T MRI examination, but the influence of implanted lumbar spine fixation devices on the RF heating sensation has not been observed. Level of Evidence : 4 Technical Efficacy : Stage 1 J. Magn. Reson. Imaging 2019;49:525–533.